Bordadoras en el museo - Del Val, Mariana (dirección); Arossa, Andrea; Colque, Analía; Albrecht, Micaela; Sandoval, Inés; Bottazzi, Ana María; Quinteros, Vanina; González, María del Carmen; Rojas, Itatí; Gallara, Cecilia Inés (2020)
Del Val, Mariana. Universidad Nacional de Córdoba. Facultad de Artes. Secretaría de Extensión; Argentina.